Systematic Review: Development Of English Modules For Physical Therapy In Improving English Language Skills For Physical Therapy Students - Ahmad Nurwanto; Melli Anisa Putri; Muhammad Rizali (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Proficiency in English is an essential skill for physiotherapy students, given the extensive medical literature published in English and the necessity for effective communication with international patients. Therefore, the development of the "English for Physiotherapy" (EFP) module is crucial for enhancing the English language capabilities of physiotherapy students. This article presents a systematic review that evaluates the effectiveness of the EFP module in improving English proficiency among these students. The methodology involves a comprehensive review of relevant studies, which indicates that the EFP module significantly enhances English skills, particularly in understanding medical literature and interacting with patients. The review demonstrates that modules specifically designed around physiotherapy terminology are more effective than general English modules, as they improve both academic comprehension and professional communication skills. The findings of this study aim to advocate for the development of more specialized English language modules within physiotherapy programs to better prepare students for the global challenges they may encounter in their practice.